Multi-scenario land use simulation and carbon storage prediction analysis in the Hainan Tropical Rainforest National Park - Chen, Zongzhu; Jiang, Xiaorong; Pan, Xiaoyan; Chen, Yiqing; Lei, Jinrui; Wu, Tingtian; Chen, Xiaohua; Li, Yuanling; Shi, Tiezhu (Frontiers in Ecology and Evolution, 2025)
BackgroundProtected areas like national parks play a pivotal role in carbon sequestration, a function essential for achieving global climate mitigation goals as climate change accelerates. However, a significant challenge lies in reconciling conservation mandates with pressures for economic growth within these regions.MethodsThe present study addresses this issue by investigating China’s Hainan Tropical Rainforest National Park (HNTRNP). By integrating 10 natural and socioeconomic variables, we applied the PLUS-InVEST model to quantify historical carbon stock dynamics from 1980 to 2020 and to project future storage capacities for 2035 under various development pathways.ResultsOur results demonstrate that: (1) In the last forty years, there has been a notable rise in forest area alongside a reduction in grassland and arable land. This shift has led to a pattern of carbon storage characterized by an initial decline of 0.65 Tg between 1980 and 2010, succeeded by a swift expansion during the period 2010–2020; (2) he geographic arrangement of carbon stocks has been largely stable, except for marked variations observed in the eastern high-altitude regions, namely Bawangling, Yinggeling, Wuzhishan, and Diaoluoshan; (3) Ecological protection policies effectively curb built land expansion and enhance carbon sequestration. By 2035, carbon storage under the ecological protection (EP) scenario is projected to reach 110.85 Tg, 1.28 Tg (1.17%) higher than the natural development (ND) scenario and 1.64 Tg (1.50%) higher than the tourism development (TD) scenario.ConclusionUltimately, this study informs future land management and conservation efforts within HNTRNP by demonstrating that sustainable socioeconomic development must be synthesized with robust ecological protection.